CALM gatekeeper training is associated with increased confidence in utilizing means reduction approaches to suicide prevention among college resident assistants. Issue 2 (8th March 2022) - Rosen, Melanie R.; Michael, Kurt D.; Jameson, J. P.
Abstract: Background: Most suicide prevention programs focus on increasing knowledge regarding the problem of suicide, yet many fail to include information on the science and application of means reduction approaches. In an attempt to address this gap in practice, the Counseling on Access to Lethal Means (CALM) program was developed to educate clinicians on the importance of means reduction interventions. Methods: In the current study, a gatekeeper CALM training was delivered to 167 resident assistants. Confidence levels regarding suicide prevention and means reduction skills were assessed at baseline, post-training, and after a 6-week follow-up. Results: Results were suggestive of medium to large training effects. Though there was a small decay of training effects at follow-up, the effects were durable when compared to baseline levels. Conclusion: Given these findings, future gatekeeper trainings should be provided more consistently to help sustain the effects and data on the implementation of CALM principles should be measured during follow-up assessments.